Tourism and Sustainable Entrepreneurship Development in Rural Areas of Central Hamadan - Seyed Hossein Shahed; Bijan Rahmani; Pegah Moridsadat (تحقیقات کاربردی علوم جغرافیایی)
Today, tourism and related jobs, with job creation, improved quality of life, income distribution and optimal utilization of resources, and thus plays an important role in rural economic development in rural development. Therefore, the main purpose of this article is to explain the components of tourism and sustainable entrepreneurship development in the rural areas of the central part of Hamadan. Research, Purpose, and Methodology The statistical population of this study was calculated according to the statistical yearbook of Hamedan province in 1395 with 524688 people (23476 households). Taken. The results show that rural tourism in the area by creating employment, increasing income levels, diversification of economic activities, social relationships spread between the host community and visitors to the protection of cultural heritage and natural environment has helped to prevent the inappropriate migration and Optimization of The earth helps sustainable rural development and, among other things, enhances government support (such as insurance, transit facilities, etc.). The tourism sector "," facilitate the setting up of tourism businesses in terms of time and cost "," reduce environmental pollution and promote environmental health in rural areas (waste management and garbage collection, sanitation, ... »greatest impact Has a range of studies on tourism development and entrepreneurship.